Analysis of secondary structure predictions of Dengue Virus Type 2 NS2B/NS3 against crystal structure to evaluate the predictive power of thein silico methods - Othman, R.; Wahab, H.A.; Yusof, R.; Rahman, N.A. (2007)
Multiple sequence alignment was performed against eight proteases from the Flaviviridae family using ClustalW to illustrate conserved domains. Two sets of prediction approaches were applied and the results compared. Firstly, secondary structure prediction was performed using available structure prediction servers. The second approach made use of the information on the secondary structures extracted from structure prediction servers, threading techniques and DSSP database of some of the templates used in the threading techniques. Consensus on the one-dimensional secondary structure of Den2 protease was obtained from each approach and evaluated against data from the recently crystallised Den2 NS2B/NS3 obtained from the Protein Data Bank (PDB). Results indicated the second approach to show higher accuracy compared to the use of prediction servers only. Thus, it is plausible that this approach is applicable to the initial stage of structural studies of proteins with low amino acid sequence homology against other available proteins in the PDB.